Las arenas de Marte - Clarke, Arthur C. (Arthur Charles), 1917-2008 (Edhasa nebulae., 2015)
When a celebrated science fiction writer takes to space on his first trip to Mars, he stumbles upon Mars' most carefully hidden secrets and threatens the future of the entire planet!